2023
DOI: 10.3390/pharmaceutics15030865
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Lactoferrin on the Ocular Surface

Abstract: Lactoferrin (LF) is a first-line defense protein with a pleiotropic functional pattern that includes anti-inflammatory, immunomodulatory, antiviral, antibacterial, and antitumoral properties. Remarkably, this iron-binding glycoprotein promotes iron retention, restricting free radical production and avoiding oxidative damage and inflammation. On the ocular surface, LF is released from corneal epithelial cells and lacrimal glands, representing a significant percentage of the total tear fluid proteins. Due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 154 publications
(235 reference statements)
0
2
0
Order By: Relevance
“…LF’s therapeutic effects include mitigating CECs damage and promoting cellular repair, as demonstrated in animal models of DED ( Pattamatta et al, 2013 ; Regueiro et al, 2023 ). Connell et al (2021) also observed that LF can increase tear secretion, inhibit the expression of inflammatory factors, and induce a short-lasting effect on tear secretion by modulating the gut microbiota to stimulate the production of short-chain FAs in a mouse model of DED.…”
Section: Impact Of Nutrients On the Ocular Surface And Potential Risksmentioning
confidence: 99%
“…LF’s therapeutic effects include mitigating CECs damage and promoting cellular repair, as demonstrated in animal models of DED ( Pattamatta et al, 2013 ; Regueiro et al, 2023 ). Connell et al (2021) also observed that LF can increase tear secretion, inhibit the expression of inflammatory factors, and induce a short-lasting effect on tear secretion by modulating the gut microbiota to stimulate the production of short-chain FAs in a mouse model of DED.…”
Section: Impact Of Nutrients On the Ocular Surface And Potential Risksmentioning
confidence: 99%
“…Despite the strong interest in clinical applications of Lf, there are just a few comprehensive clinical studies on topical, ophthalmic Lf formulations [ 92 ] ( Table 2 ).…”
Section: Strategies For Ocular Delivery Of Lfmentioning
confidence: 99%
“…Lactoferrin possesses immunomodulatory, anti-inflammatory, antioxidant, antiviral, antimicrobial and anticancerogenic activities. Lately, various technologies have been developed to advance the lactoferrin's role in the ocular drug bioavailability (Figure 6) [58]. 2.1.9.…”
Section: Lactoferrinmentioning
confidence: 99%